RAFT polymer cross-coupling with boronic acids. Issue 37 (13th August 2018) - Golf, Hartwig; O'Shea, Riley; Braybrook, Carl; Hutt, Oliver; Lupton, David W.; Hooper, Joel F.
Abstract : A one step modification of RAFT polymers to give functionalised materials. Abstract : The ability to modify the thiocarbonylthio end-groups of RAFT polymers is important for applications where an inert or highly functionalised material is required. Here we report a copper promoted cross-coupling reaction between RAFT polymer end-groups and aryl boronic acids. This method gives high conversion to the modified polymers, and is compatible with a wide variety of functional molecules.